Reliability Analysis of Hybrid Energy Systems: Case Study of Davutpasa Campus - Kekezoglu, B.; Arikan, O.; Erduman, A.; Isen, E.; Durusu, A.; Bozkurt, A. (IEEE, 2013)
In recent years, sustainable and clean renewable energy resources are widely used instead of fossil fuel energy resources in electrical energy generation systems. Especially, wind and solar energy conversion systems are utilized together in stand-alone systems. in this study, reliability analysis of a hybrid system installed in Davutpasa Campus of Yildiz Technical University is investigated. The system includes a wind turbine, PV panels, a hybrid charge regulator, a MPNT charge controller, an inverter, battery group and loads. Reliability indexes are calculated for analyzed system. The obtained results are examined and presented in this paper.
Keywords: renewable energy sources; hybrid systems; reliability; loss of load expectation; loss of energy expectation; Computer Science; Telecommunications